ANALYZING THE EFFICIENCY AND PRODUCTIVITY OF WAQF FUND MANAGEMENT IN INDONESIA AND MALAYSIA: A DEA AND MPI APPROACH - Maulida, Syahdatul (Universitas Airlangga, 2025)
Many waqf institutions face challenges when optimizing their performance due to varying capacities and operational conditions. The present research analyses the productivity and efficiency of the management of waqf funds in Indonesia and Malaysia from 2018 to 2023. This research employs data extracted from the annual reports of waqf management organizations. The data was analyzed using the DEAP 2.1 software regarding Data Envelopment Analysis and the Malmquist Productivity Index, which provided a larger comparative view of both the efficiency and productivity of waqf funds over time. During the observation period, we found that the average Total Factor Productivity Change (TFPCH) was 0.956, which shows a small dip in productivity. The main factor driving this productivity was technological change (TECHCH), which registered at 1.096, whereas the impact from technical efficiency (EFFCH) was pretty limited at 0.872. The analysis shows that in Indonesia, we should really work on making waqf distribution better, keep the operational costs in check, boosting waqf collection, and ensuring that assets are used efficiently. In Malaysia, the biggest areas to improve are waqf collection and distribution, while it seems like operational costs and asset management are in pretty good shape already. These findings offer valuable insights for policymakers and waqf institutions, highlighting the importance of improving technology and efficiency to better manage and sustain waqf funds in both countries.